CO-induced Pd segregation and the effect of subsurface Pd on CO adsorption on CuPd surfaces. (14th November 2016) - Padama, A A B; Villaos, R A B; Albia, J R; Diño, W A; Nakanishi, H; Kasai, H
Abstract: We report results of our study on the adsorption of CO on CuPd surfaces with bulk stoichiometric and nonstoichiometric layers using density functional theory (DFT). We found that the presence of Pd atoms in the subsurface layer promotes the adsorption of CO. We also observed CO-induced Pd segregation on the CuPd surface and we attribute this to the strong CO–Pd interaction. Lastly, we showed that the adsorption of CO promotes Pd–Pd interaction as compared to the pristine surface which promotes strong Cu–Pd interaction. These results indicate that CO adsorption on CuPd surfaces can be tuned by taking advantage of the CO-induced segregation and by considering the role of subsurface Pd atoms.